1032-P: Diabetes Technology Utilization and eHealth Literacy in Patients with Type 1 Diabetes - PARIMI, NEHA; ZADE, DANIEL; BROMBERGER, LEE A.; SIDHAYE, ANIKET; BROWN, ELIZABETH A.; WOLF, RISA M.; MATHIOUDAKIS, NESTORAS N. (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: Type 1 Diabetes (T1D) requires continuous self-management to maintain glycemic control. Higher health literacy is associated with greater self-efficacy and diabetes management. There is limited data on health literacy and diabetes technology use. This study aimed to determine if e-health literacy is associated with technology use in patients with T1D who are not currently using technology optimally. Methods: This prospective survey study included patients with T1D who were not using diabetes technology or were using technology sub-optimally. Patients were enrolled at the Johns Hopkins Diabetes Center from February to December 2024. The 8 item E-Heals survey was administered to assess health literacy, with higher score (highest being 40) representing greater health literacy. Chi-Square, Fisher Exact and Wilcoxon rank sum tests evaluated the associations between demographics, technology use and health literacy. Results: Participants included 147 individuals (73 adults, 74 children and adolescents, median age 20.0 years, 58.5% males, 40.1% Black, 5.4% Hispanic). The mean HbA1c was 8.8%. In the cohort, 68.7 % were using technology sub-optimally and 31.3% were not on any diabetes technology. Mean health literacy score was 32.5 (SD=5.5). There were no significant differences in mean E-Heals scores by diabetes technology use: sub-optimal technology = 32.7(SD=5.4) vs no technology = 31.9 (SD=5.9), p-value=0.47. No significant differences were observed in the reported e-health literacy based on age, sex, race, ethnicity, insurance type, income, or education level. Conclusion: We did not find an association between e-health literacy and use of diabetes technology. There are likely other socio-demographic and systemic factors that impact diabetes technology access and use.